Religion and the Construction of Political Legitimacy in Medieval Europe with Lessons for Organizational Governance - Arafah, Nasriani; Azkari, Ridha; Renaldi, Renaldi (Journal Social Humanity Perspective, 2024)
This current enquiry questions the role of religion to political authority and organisational governance in medieval Europe utilising a qualitative historical research method and inference analysis to understand the level to which the ecclesiastical endorsement, ritual practice and institutionalised legitimacy affected the stability of political authority. These findings show that ecclesiastical power, that of the Church in the first place continued to provide the greatest means of legitimising rulers and often overshadowed military and fiscal capabilities in respect to determinate power. Symbolic customs and aboveboard punishments by the Church provided rulers with not only cultural rationalisation but also organisational entrenchment allowing weak polities to endure rule in the decades of warfare and scarcity. Taken together, these results emphasise the importance of legitimacy as a non-material resource in political and organisational systems to problematise materialist power explanations. In the light of management studies, similarities to current organisational practice can be drawn: contemporary business, much like its medieval equivalent, relies on symbolic capital, narrative processes and legitimacy to build power and to generate stability and strength. Thus, medieval Church can be considered one of the enlighteners in legitimacy management process that also helps to depict how in adherence to values, beliefs and institutional control is the basis of governance, regardless of the historical time.